2006
DOI: 10.1152/ajprenal.00126.2005
|View full text |Cite
|
Sign up to set email alerts
|

FXYD proteins: new regulators of Na-K-ATPase

Abstract: FXYD proteins belong to a family of small-membrane proteins. Recent experimental evidence suggests that at least five of the seven members of this family, FXYD1 (phospholemman), FXYD2 (gamma-subunit of Na-K-ATPase), FXYD3 (Mat-8), FXYD4 (CHIF), and FXYD7, are auxiliary subunits of Na-K-ATPase and regulate Na-K-ATPase activity in a tissue- and isoform-specific way. These results highlight the complexity of the regulation of Na+ and K+ handling by Na-K-ATPase, which is necessary to ensure appropriate tissue func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
316
0
11

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 329 publications
(332 citation statements)
references
References 101 publications
(127 reference statements)
5
316
0
11
Order By: Relevance
“…In addition, Fxyd3 (formerly Mat-8) also showed reduced expression. Fxyd3 has been implicated in ion channel regulation, where it may regulate the Na ϩ and K ϩ balance in and around cells (21). There were also large differences in the expression of glycosylation enzymes, suggesting qualitative and quantitative differences in the carbohydrate moieties on glycoproteins and glycolipids (Tables 1 and 2).…”
Section: Altered Cell-cell and Cell-extracellular Matrix (Ecm) Interamentioning
confidence: 99%
“…In addition, Fxyd3 (formerly Mat-8) also showed reduced expression. Fxyd3 has been implicated in ion channel regulation, where it may regulate the Na ϩ and K ϩ balance in and around cells (21). There were also large differences in the expression of glycosylation enzymes, suggesting qualitative and quantitative differences in the carbohydrate moieties on glycoproteins and glycolipids (Tables 1 and 2).…”
Section: Altered Cell-cell and Cell-extracellular Matrix (Ecm) Interamentioning
confidence: 99%
“…However, unlike with SERCA, there is no evidence for phosphorylation of this protein in the resting platelet phosphoproteome [47], although given the need for activation with a strong platelet activator for the Na + /K + -ATPase to be influenced by PKC, phosphorylation of this protein might not be expected under resting conditions. In cardiac muscle and several other cell types, Na + /K + -ATPase activity is modulated by association with members of the FXYD family of proteins [55]. However, no members of the FXYD family have been detected in the platelet proteome [56].…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Previous studies have shown that the FXYD2 protein is highly enriched in kidney tissue. 17 Furthermore, it is expressed specifically in the distal nephron.…”
mentioning
confidence: 99%